P-009 WEB Endovascular Treatment of Wide-neck Bifurcation Aneurysms: Short- and Midterm Results in a European Study. (26th July 2014) - Pierot, L; Klisch, J; Gauvrit, J; Szikora, I; Leonardi, M; Liebig, T; Nunzi, N; Boccardi, E; Di Paola, F; Holtmanspötter, M; Weber, W; Calgliari, E; et al.
Abstract : Background and purpose: Flow disruption with the WEB-DL device has been used safely for the treatment of wide-necked bifurcation aneurysms but the stability of aneurysm occlusion after this treatment is unknown. This retrospective multicenter European study analyzed short- and midterm data in patients treated with WEB-DL. Methods: Twelve European neurointerventional centers participated to the study. Clinical data, pre- and post-operative, short-, and midterm images were collected. An experienced interventional neuroradiologist independently analyzed images. Aneurysm occlusion was classified in 4 grades: complete occlusion, opacification of the proximal recess of the device, neck remnant, and aneurysm remnant. Results: Forty-five patients (34 females and 11 males) aged 35 to 74 years (mean: 56.3 +/- 9.6 years) harbouring 45 aneurysms treated with the WEB device were included. Aneurysm locations were middle cerebral artery in 26 patients, posterior circulation in 13, anterior communicating artery in 5, and internal carotid artery terminus in 1. Forty-two aneurysms were unruptured. Good clinical outcome (mRS < 2) was observed in 93.3% of patients. Adequate occlusion (Complete occlusion, opacification of the proximal recess, or neck remnant) was observed in 30/37 patients (81.1%) in short-term follow-up (median 6 months) and in 26/29 patients (89.7%) in midterm follow-up (median 13 months). Worsening of aneurysm occlusion was observed in 2/28 patients (7.1%) in midterm follow-up. Conclusions: The results suggest WEB treatment of wide-neck bifurcation aneurysms offers stable occlusion in aneurysms that are usually unstable. Additionally, our data show that opacification of the WEB recess can be delineated from true neck or aneurysm remnant. Disclosures: L. Pierot: 2; C; Sequent. J. Klisch: None. J. Gauvrit: None. I. Szikora: None. M. Leonardi: None. T. Liebig: None. N. Nunzi: None. E. Boccardi: None. F. Di Paola: None. M. Holtmanspötter: None. W. Weber: None. E. Calgliari: None. B. Lubicz: None.